Clinical protocol for esthetic restoration using a self-etching adhesive - Tonetto, Mateus Rodrigues [UNESP]; Borges, Fausto Frizzera [UNESP]; Fontanari, Lucas [UNESP]; Borges, Alvaro Hnerique; Bandéca, Matheus Coelho; Andrade, Marcelo Ferrarezi de [UNESP] (Jaypee Brothers Medical Publishing, 2013)
The advent of new adhesive systems is making techniques and clinical protocols to become faster and simpler, however it does not reduce the importance of knowledge of the properties, characteristics and interaction of dental materials with the tooth structure. Among the adhesives that have recently emerged, highlight the self-etching systems, especially the two-step selfetching, in which the acid primer is available in a separate bottle from the adhesive. These adhesives have shown good results for bond strength, microleakage and postoperative sensitivity, being an option for direct adhesive restorations in anterior teeth. This way, the present case report describes the step-by-step making of a class IV restoration in an upper right central incisor using atwo-step adhesive system, obtaining satisfactory results.
Keywords: Dental esthetics; Dental bonding; Permanent dental restoration